(3bghI GdEfTGAs - (3CHh HcQ Hf Ydj Hf YHO Gddg GdMehj GdCRQGQj, Jbj GdOjf GHf MLI,J (B837 (3g` s
(3ChdgG (B:s
(3hHYO, aEfj (B[(3eG(B] (3GOQJ cCS GdEfTGA gfG EdG djWjH GdJCed Hfbdg ef TWhW GdLhRGA Edi GdJCfj aj QjGV GdefKhQ s
(3BNQgG (B:s
(3hPcQ GdbGVj TeS GdOjf GHf NdcGf aj JGQjNg s
(3GfXQ GdLRA GdChd GdQbe (B666 (3COHs
(3QSGFd hJbGdjO SdWGfjIs
(3cJHJ GdYfhGfGJ HGdMeQIs
(3hHgG fXGe GdJYbjHIs
(3hHgG VHW s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs